Expression of interleukin-18, interferon-γ and interleukin-10 in hepatocellular carcinoma - Chia, Chok Seng; Ban, Kechen; Ithnin, Hairuszah; Singh, Harjit; Krishnan, R; Mokhtar, Suryati; Malihan, Nik; Seow, Heng Fong (Elsevier, 2002)
This is the first report on the detection of IL-18, IFN-γ and IL-10 proteins in hepatocelllular carcinoma. In the apparently normal surrounding tissue, 13 out of 17 paired specimens showed positive immunoreactivity to IL-18 (76.5%) compared with six out of 17 in the tumour portion (35.3% of specimens). Thus, a significantly higher number of IL-18 positive specimens was found in the hepatocytes of apparently normal surrounding tissue compared with the tumour (P=0.018). In contrast, the number of specimens with positive immunoreactivity to the antibody against the Th1 cytokine, IFN-γ expression in the hepatocytes was lower. Only one specimen from the apparently normal surrounding tissue (one out of 17; 5.9%) and three other specimens from the tumour portion (three out of 17; 17.6%) had positive immunoreactivity. Similarly, the expression of the Th2 cytokine, IL-10 in normal (four out of 17; 23.5%) and tumour portions (five out of 17; 29.4%) was also low. Thus, there did not appear to be predominant Th2 immune response as denoted by IL-10 expression. Using the Spearman correlation rank test, a significant correlation between IL-18 expression in the apparently normal surrounding tissue and high α-foetoprotein (AFP) levels of >350 IU/l. No correlation between IL-18 expression in the tumour portion and clinicopathological factors was found. There was also no correlation found between IL-18 and the other cytokines, namely, IFN-γ and IL-10 expression These new findings provide additional information on the type of cytokines expressed in the tumour microenvironment and give a further insight into the role of cytokines in the pathogenesis of cancer which is critical for the development of effective immunotherapeutic approaches for cancer therapy in the future.